Prehospital Triage of Acute Stroke Patients During the COVID-19 Pandemic. Issue 7 (July 2020) - Goyal, Mayank; Ospel, Johanna M.; Southerland, Andrew M.; Wira, Charles; Amin-Hanjani, Sepideh; Fraser, Justin F.; Panagos, Peter
Abstract : Abstract: The coronavirus disease 2019 (COVID-19) pandemic has broad implications on stroke patient triage. Emergency medical services providers have to ensure timely transfer of patients while minimizing the risk of infectious exposure for themselves, their co-workers, and other patients. This statement paper provides a conceptual framework for acute stroke patient triage and transfer during the COVID-19 pandemic and similar healthcare emergencies in the future.